The Institutional Design Frontiers of Publicness and University Performance. (4th August 2016) - Anderson, Derrick; Whitford, Andrew
Abstract: This introduction to the symposium on the institutional design frontiers of publicness and university performance summarizes the range of diverse intellectual and practical perspectives converging on the idea that issues of design and publicness are important for thinking about the future of higher education. Collectively, the articles featured in this symposium demonstrate that the challenges facing higher education exhibit assorted social, economic, and political complexities. Public administration perspectives can play a key role in understanding and reshaping our higher education system into a more responsive social enterprise .